Efficacy evaluation of photodynamic therapy for oral lichen planus: a systematic review and meta-analysis - He, Yuqing (BMC Oral Health, 2020)
BACKGROUND: Photodynamic therapy (PDT) is a new option for oral lichen planus (OLP) management; however, there are different opinions on the efficacy of PDT for OLP. The aim of this study was to comprehensively assess the efficacy of PDT in the treatment of OLP and compare PDT with steroid therapy. METHODS: A systematic review and meta-analysis were conducted to assess the curative effect of PDT. Five electronic databases were searched, PubMed, Web of Science, the Cochrane Library, Embase, and EBSCO up to 1 December, 2019. Random and fixed effects models for pooled estimates calculation were used and the Meta package of R was applied. RESULTS: Pooled estimates revealed that, after PDT, the lesion size decreased by 1.53 cm(2) (95% confidence interval (CI): 0.71–2.35) after PDT and the partial response (PR) was 0.77 (95% CI: 0.65–0.85). The visual analogue scale (VAS) score decreased by 3.82 (95% CI: 2.80–4.85) and the Thongprasom sign score decreased by 1.33 (95% CI: 0.56–2.10) after PDT. Subgroup analyses revealed that the 5-aminolevulinic acid (5-ALA) was more effective than methylene blue (MB), with a PR of 0.87 (95% CI: 0.80–0.91). The topical use of 5-ALA yielded a better response than gargling methylene blue. In terms of VAS, the diode laser showed a better clinical PR in the treatment of OLP. In terms of changes in lesion size, the efficacy of the semiconductor laser was higher than that of the diode laser. PDT had a similar efficacy to topical corticosteroids, as shown by pooled estimates of five randomised controlled trials with 139 lesions. CONCLUSION: This systematic review indicates that PDT is an effective treatment modality for the management of OLP. PDT is as effective as topical corticosteroid in the treatment of OLP and could be used for cases resistant to steroids or when steroids are contraindicated.